Investigating the benefits and challenges of including bereaved women in research: a multifaceted perinatal audit in a socially disadvantaged French district. Issue 9 (23rd September 2020) - Sauvegrain, Priscille; Zeitlin, Jennifer
Abstract : Objectives: To describe experiences including interviews with bereaved women in a clinical audit. Design: The data come from an audit of all stillbirths and neonatal deaths at ≥22 weeks of gestation in Seine-Saint-Denis, a disadvantaged French district in 2014. We included bereaved women using a questionnaire that also contained open-ended questions administered in an interview format by a midwife-investigator several weeks after the death. The study included a referral protocol for bereaved women with unmet needs revealed during the interviews. A psychological support for the three midwife-investigators was set-up, in the form of a support group. Setting: The 11 maternity hospitals in the district. Participants: 218 women (227 deaths). Analyses: Data come from medical records, maternal interviews, the reviews of the audit's expert panel and written narratives of their experiences provided by the midwife-investigators. Quantitative data were analysed statistically, and qualitative data thematically. Results: One-third (75) of the women agreed to an interview, but acceptance ranged from 6% to 60% by maternity unit. Characteristics of respondents and non-respondents were similar. Members of the audit's expert panel reported that 41% of the interviews contained new information relevant to their assessment. Of the women interviewed, 35% were referred to a medical professional, psychologist or social worker. Midwife-investigators' experiences illustrated the benefits of a support group with three main themes identified: improving their interactions with bereaved women as well as medical teams and protecting their psychological well-being. Conclusion: These results showed that including interviews with bereaved women in audit designs was feasible and provided valuable information on women's care and social circumstances that were not available in medical records. They also highlight the importance of implementing referral protocols for the bereaved women, used in over one-third of cases, as well as providing support for study investigators.